1996
DOI: 10.1007/bf01691312
|View full text |Cite
|
Sign up to set email alerts
|

Study ofPseudomonas aeruginosa serotype O12 isolates with a common antibiotic susceptibility pattern

Abstract: A multicentre European study of Pseudomonas aeruginosa serotype O12 isolates with a common antibiotic resistance pattern was conducted. Resistance to beta-lactams and aminoglycosides was observed in 24 of the 25 isolates, as often reported in Europe, and all 25 isolates were significantly more susceptible to fosfomycin than 189 isolates of other serotypes (72% vs. 13.2%). The mutational frequency of serotype O12 was similar to that of other serotypes and thus could not explain the susceptibility to fosfomycin.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Nineteen studies in total provided data on the susceptibility to fosfomycin of MDR P. aeruginosa isolates [8][9][10][11][12][14][15][16][18][19][20][21][23][24][25][26][28][29][30]. Seven of these nineteen studies found that ≥90% of the isolates evaluated were susceptible to fosfomycin [10][11][12]19,21,23,29] and four additional studies found that 50-90% of the isolates were susceptible to fosfomycin [8,15,24,28].…”
Section: Microbiological Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Nineteen studies in total provided data on the susceptibility to fosfomycin of MDR P. aeruginosa isolates [8][9][10][11][12][14][15][16][18][19][20][21][23][24][25][26][28][29][30]. Seven of these nineteen studies found that ≥90% of the isolates evaluated were susceptible to fosfomycin [10][11][12]19,21,23,29] and four additional studies found that 50-90% of the isolates were susceptible to fosfomycin [8,15,24,28].…”
Section: Microbiological Studiesmentioning
confidence: 99%
“…Regarding the interpretative MIC breakpoints of susceptibility to fosfomycin used, eight studies used a susceptibility breakpoint of ≤64 mg/L [8,11,12,14,16,17,21,27], four studies used a breakpoint of ≤32 mg/L [23,24,28,29], one study used a breakpoint of ≤16 mg/L [18], whereas specific data were not reported in 10 studies [9,10,13,15,19,20,22,25,26,30]. The majority of the latter (six of ten) were performed in France [9,10,15,20,25,26].…”
Section: Microbiological Studiesmentioning
confidence: 99%
See 3 more Smart Citations